The Evolution of Technology in Digital Business Transformation and Its Impact on Consumer Behavior - Kusumastuti, Anggit Dyah; Mutiasari, Annisa Indah; Astuti, Ariyani Dwi (Electronic Journal of Education, Social Economics and Technology, 2025)
Business actors in the digital era today are required to innovate and adapt to the ever-changing demands of consumers. To keep up with the competition and remain relevant in the market, digital transformation is needed to support business existence. This research aims to understand how the implementation of business digital transformation affects consumer behaviour and how the establishment of business strategies influences consumer behaviour. This type of research is descriptive with a quantitative approach. Quantitative research with a comparative approach. The research data sources include primary data obtained from the distribution of questionnaires and secondary data through e-commerce development data, household consumption data for 2000 – 2023, and community consumption component data with comparative data for 2008 and 2018, as well as determining business strategies. The research sample consisted of 100 respondents using an accidental sampling technique. The variance analysis in this study uses SEM-PLS, or Structural Equation Modeling with Partial Least Square. The research results show that digital transformation affects consumer behaviour. Transformation has the potential to positively impact productivity and drive inclusive economic growth and business sustainability. Business strategies influence consumer behaviour. A good plan allows companies to be more responsive to changes in consumer needs, create attractive differentiation, and leverage technology to provide a better experience. Therefore, having a clear and focused competitive strategy is crucial to ensure the company remains competitive and relevant in the ever-changing market.